Manifestations of the Efimov effect for three identical bosons - D’Incao, J. P.; Esry, B. D. (My University, 2005)
We present numerical solutions of the Schrödinger equation for three identical bosons from very large to essentially infinite two-body s-wave scattering lengths a. We have considered scattering lengths up to 2×105a.u. and solved the hyperangular part of the Schrödinger equation for distances up to 106a.u. From these, we obtained the three-body effective potentials, hyperspherical channel functions and the asymptotic behavior of the nonadiabatic couplings in order to characterize the main aspects of the Efimov states. These results allow us to test and quantify the assumptions related to the Efimov effect.